1982
DOI: 10.1111/j.1365-2842.1982.tb00542.x
|View full text |Cite
|
Sign up to set email alerts
|

A more efficient biofeedback procedure for the treatment of nocturnal bruxism

Abstract: The study describes a noval approach in the use of a conditioning procedure for the treatment of nocturnal bruxism. The effectiveness of the procedure is demonstrated through its application with two nocturnal bruxists in controlled study designs. Subject 1 received several variations of this procedure and the result indicated that using a loud tone which she manually reset after awakening was the most effective approach to this treatment. The second study was designed to compare the effectiveness of relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
6

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 6 publications
(1 reference statement)
0
11
0
6
Order By: Relevance
“…In two studies, biofeedback induced a decrease in the duration but not the frequency of bruxing episodes [104,105]: this suggests little evidence of learning. However, in other studies a reduction in both duration and num ber of bruxing episodes was observed [94,106], Further research is needed to clarify this point. A problem with biofeedback treatment is that in the majority of studies bruxing activ ity returns to pretreatment levels soon after discontinuing the treatment [77, 91.…”
Section: Bruxismmentioning
confidence: 82%
“…In two studies, biofeedback induced a decrease in the duration but not the frequency of bruxing episodes [104,105]: this suggests little evidence of learning. However, in other studies a reduction in both duration and num ber of bruxing episodes was observed [94,106], Further research is needed to clarify this point. A problem with biofeedback treatment is that in the majority of studies bruxing activ ity returns to pretreatment levels soon after discontinuing the treatment [77, 91.…”
Section: Bruxismmentioning
confidence: 82%
“…Behavioral strategies are based on relaxation, biofeedback, and hypnosis. Although some bruxers refer a sensation of well-being, no persistent or clear effects have been obtained with this approach [181,182]. Obviously, standard sleep hygiene should be recommended for patients affected by sleep bruxism.…”
Section: Treatmentmentioning
confidence: 99%
“…• Stress reduction [34], relaxation, biofeedback [35,36], hypnosis [37], and improvement of sleep hygiene have been tried with no persistent or significant improvement. • The most prominent interventions for sleep bruxism are occlusal appliances, such as night guards for protection of teeth.…”
Section: Treatment Of Sleep Bruxismmentioning
confidence: 99%